Analisis Beban Kerja Fisik Area Liquiverter Line Beverage Pada Industri Beverage (Minuman Berperisa) - Sitorus , Tosty Maylangi; Helmi, Adlina Safitri (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2025)
The beverage industry (flavored beverages) is located in West Java, has a mechanized production process using automation and robotics systems. However, in practice there are still activities that are carried out manually, including the process of pouring sugar into the beverage dilution section. In this area there are several ingredients that are mixed, such as sugar and additives, where sugar is poured manually through the T71 tank. Work in this section is carried out by operators who must manually move the sugar pile ± 1 meter closer to the T71 tank, totaling 126 sacks of sugar for one of the products. Regulation of the Minister of Manpower of the Republic of Indonesia Number 5 of 2018, namely physical workload analysis using the Recommended Weight Limit (RWL) and Lifting Index (LI) calculations, is a reference for companies in controlling the workforce to reduce health complaints. Therefore, physical workload analysis will be carried out using the RWL and LI methods on beverage liquiverter section operators, as a form of assessment that has not been done by the industry in the sugar pouring process in the beverage liquiverter section. The LI value obtained is 3.6012 with a high level of risk. Furthermore, from the NIOSH perspective, working with LI≥3 means that the weight of the load lifted exceeds the recommended lifting limit, which is 6,942 kg (RWL), thus posing a risk of spinal injury to the operator. Suggestions as an effort to improve and control the risks of manual material handling based on the literature are the use of checklists to identify the risks of work accidents due to manual material handling, the implementation of safety lectures to improve operator understanding, and the design of workstations.